2010
DOI: 10.1007/s11120-010-9542-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative sequence analysis of CP12, a small protein involved in the formation of a Calvin cycle complex in photosynthetic organisms

Abstract: CP12, a small intrinsically unstructured protein, plays an important role in the regulation of the Calvin cycle by forming a complex with phosphoribulokinase (PRK) and glyceraldehyde-3-phosphate dehydrogenase (GAPDH). An extensive search in databases revealed 129 protein sequences from, higher plants, mosses and liverworts, different groups of eukaryotic algae and cyanobacteria. CP12 was identified throughout the Plantae, apart from in the Prasinophyceae. Within the Chromalveolata, two putative CP12 proteins h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
97
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 60 publications
(100 citation statements)
references
References 52 publications
(83 reference statements)
2
97
0
Order By: Relevance
“…This core sequence is implicated in GAPDH binding by trypsinprotection experiments (Lebreton et al, 2006); however, this region of CP12 is not visible in the electron density of either of the CP12-GAPDH structures (Matsumura et al, 2011;Fermani et al, 2012). Additionally, the N-terminal Gly-24, Ser-27, and His-46 and C-terminal Pro-65 residues are strongly conserved among all CP12 homologs (including those from eukaryotes), while the Gln-41 and Phe-57 residues following the AWD_VEEL sequence that have previously been noted as specific to cyanobacteria (Groben et al, 2010) are not strongly conserved among all cyanobacterial variants ( Fig. 2A).…”
Section: Classification Of Cyanobacterial Cp12 Types and Comparison Omentioning
confidence: 86%
See 2 more Smart Citations
“…This core sequence is implicated in GAPDH binding by trypsinprotection experiments (Lebreton et al, 2006); however, this region of CP12 is not visible in the electron density of either of the CP12-GAPDH structures (Matsumura et al, 2011;Fermani et al, 2012). Additionally, the N-terminal Gly-24, Ser-27, and His-46 and C-terminal Pro-65 residues are strongly conserved among all CP12 homologs (including those from eukaryotes), while the Gln-41 and Phe-57 residues following the AWD_VEEL sequence that have previously been noted as specific to cyanobacteria (Groben et al, 2010) are not strongly conserved among all cyanobacterial variants ( Fig. 2A).…”
Section: Classification Of Cyanobacterial Cp12 Types and Comparison Omentioning
confidence: 86%
“…PRK is very similar to another enzyme, uridine kinase, and annotations, COG (for Cluster of Orthologous Groups), and pfam assignments frequently contradict one another, suggesting that such computationally based functional assignments for this gene product are unreliable. However, it is clear that among the CP12 variants, the N terminus, which has been shown to interact with PRK (Groben et al, 2010), is overall less conserved than the GAPDH-interacting C terminus ( Fig. 2A).…”
Section: Evidence Of Differential Interaction Of Cyanobacterial Cp12mentioning
confidence: 99%
See 1 more Smart Citation
“…Given the complexity of the metabolic and developmental phenotype in the antisense plants, however, it is possible that CP12 may have additional functions. Bioinformatic and experimental evidence has shown that CP12 is an intrinsically unstructured protein (Graciet et al, 2003;Gardebien et al, 2006;Marri et al, 2009;Groben et al, 2010). Such proteins can have multiple partners and are frequently considered to be regulatory hubs (Tompa, 2002;Dunker et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…There are also differences among algae in the regulation of enzymes of the PCRC [63]. Further work is needed to establish the relevance, if any, of atmospheric changes to these differences in the regulation of enzymes of the PCRC [63,64], and also the absence of Rubisco activase from algae with the form ID Rubisco in the few cases examined [61].…”
Section: Rubisco Carboxylase Activity and The Photosynthetic Carbon Rmentioning
confidence: 99%